1999
DOI: 10.1177/014572179902500107
|View full text |Cite
|
Sign up to set email alerts
|

A Computerized Model for Home Glucose Monitoring Proficiency Testing: Efficacy of an Innovative Testing Program

Abstract: An annual methodology evaluation such as the one in this study should become a standard of care to identify patients for remedial classes to correct the source of error. The goal must be to meet or exceed the American Diabetes Association standard of 15% total error in home glucose monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…The study revealed two kinds of errors that were quite frequent: errors that falsify the measurement reading as well as errors that can have a negative effect on patient compliance. In the reference literature there is a consensus that individuals with diabetes make numerous mistakes in the self- monitoring of their blood glucose levels and that remedial training sessions are required 22,23,24,25,26,27,28,29,30,33,34,38,39. But there is little data on how much impact to expect from these remedial training sessions for type 2 diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study revealed two kinds of errors that were quite frequent: errors that falsify the measurement reading as well as errors that can have a negative effect on patient compliance. In the reference literature there is a consensus that individuals with diabetes make numerous mistakes in the self- monitoring of their blood glucose levels and that remedial training sessions are required 22,23,24,25,26,27,28,29,30,33,34,38,39. But there is little data on how much impact to expect from these remedial training sessions for type 2 diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Alto et al found deviations of over 20% in 16% of the study participants22 and Kabadi et al found greater deviations in 25% of the participants 24. In the studies of Bergenstal and Schrot et al, 19% and 31%, respectively, of the readings deviated more than 15% from the control reading 27,30…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The split-sample design is commonly used for quality control of POC instruments at hospitals or in GPs offices (104)(105)(106)(107).…”
Section: Split Sample Designmentioning
confidence: 99%
“…[25] In 2004, €3.9 billion were spent on the SMBG worldwide, with a yearly growth rate of 11.5%. Researchers and patient organizations [25,[28][29][30][31][32] state that patients' measurements should be assessed regularly. In comparison, that same year the amount spent on drugs to lower blood glucose, including insulin, was approximately €52 million.…”
Section: Introductionmentioning
confidence: 99%